127k views
3 votes
Use f(x) = 2 x and f-'(x) = 2x to solve the problems.

f(2)=...
F1 (1) =...
F1 (12)) = ...

Use f(x) = 2 x and f-'(x) = 2x to solve the problems. f(2)=... F1 (1) =... F1 (12)) = ...-example-1

1 Answer

2 votes

Answer:

a) 1

b) 2

c) 2

Explanation:

a)
f(2) means find the output for
(1)/(2)x when
x=2.


(1)/(2)(2)


(2)/(2)


1

b)
f^(-1)(1) means find the output for
2x when
x=1


2(1)


2

c) If
f and
f^(-1) are truly inverses then
f(f^(-1)(u))=u and
f^(-1)(f(u))=u as long as
u satisfies the domains.

So we should be able to conclude that
f^(-1)(f(2))=2 with no work.

However, I will also show work.


f^(-1)(f(2))


f^(-1)(1) since
f(2)=1 from part a.


2 since
f^(-1)(1)=2 from part b.

User Rashim
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.